Risk of Ischemic Stroke in Patients With Atrial Fibrillation After Extracranial Hemorrhage. Issue 12 (December 2020) - Zhou, Eric; Lord, Aaron; Boehme, Amelia; Henninger, Nils; de Havenon, Adam; Vahidy, Farhaan; Ishida, Koto; Torres, Jose; Mistry, Eva A.; Mac Grory, Brian; Sheth, Kevin N.; Gurol, M. Edip; et al.
Abstract : Background and Purpose: Anticoagulation therapy not only reduces the risk of ischemic stroke in atrial fibrillation (AF) but also predisposes patients to hemorrhagic complications. There is limited knowledge on the risk of first-ever ischemic stroke in patients with AF after extracranial hemorrhage (ECH). Methods: We conducted a retrospective study using the California State Inpatient Database including all nonfederal hospital admissions in California from 2005 to 2011. The exposure variable was hospitalization with a diagnosis of ECH with a previous diagnosis of AF. The outcome variable was a subsequent hospitalization with acute ischemic stroke. We excluded patients with stroke before or at the time of ECH diagnosis. We calculated adjusted hazard ratios for ischemic stroke during follow-up and at 6-month intervals using Cox regression models adjusted for pertinent demographics and comorbidities. In subgroup analyses, subjects were stratified by primary ECH diagnosis, severity/type of ECH, age, CHA2 DS2 -VASc score, or the presence/absence of a gastrointestinal or genitourinary cancer. Results: We identified 764 257 patients with AF (mean age 75 years, 49% women) without a documented history of stroke. Of these, 98 647 (13%) had an ECH-associated hospitalization, and 22 748 patients (3%) developed an ischemic stroke during the study period. Compared to patients without ECH, subjects with ECH had ≈15% higher rate of ischemic stroke (overall adjusted hazard ratio, 1.15 [95% CI, 1.11–1.19]). The risk appeared to remain elevated for at least 18 months after the index ECH. In subgroup analyses, the risk was highest in subjects with a primary admission diagnosis of ECH, severe ECH, gastrointestinal-type ECH, with gastrointestinal or genitourinary cancer, and age ≥60 years. Conclusions: Patients with AF hospitalized with ECH may have a slightly elevated risk for future ischemic stroke. Particular consideration should be given to the optimal balance between the benefits and risks of anticoagulation therapy and the use of nonanticoagulant alternatives, such as left atrial appendage closure in this vulnerable population. Abstract : Supplemental Digital Content is available in the text.